Growth performance and wood quality of white jabon (Neolamarckia cadamba) progeny testing at Parung Panjang, Bogor, Indonesia - Nurul Chaerani; DEDE J SUDRAJAT; ISKANDAR Z SIREGAR; ULFAH J SIREGAR (Society for Indonesian Biodiversity, 2019)
Abstract. Chaerani N, Sudrajat DJ, Siregar IZ, Siregar UJ. 2019. Growth performance and wood quality of white jabon (Neolamarckia cadamba) progeny testing at Parung Panjang, Bogor, Indonesia. Biodiversitas 20: 2295-2301. The aim of this study was to evaluate the genetic parameters of growth and wood quality in white jabon progeny test at 54 months old in Parung Panjang, Bogor. The 105 half-sib families obtained from 12 provenances were evaluated in a randomized complete block design with five replications. Wood quality was assessed both in a non-destructive way using a pilodyn and by destructive method using wood sample taker. Results indicated that the mean value ranged from 5.10 to 10.15 m for height, 6.67 to 15.30 cm for diameter, 2.30 to 3.62 cm for pilodyn penetration, 0.66 to 0.82 g/cm3 for wood density, 0.33 to 0.50 for specific gravity, and 66 to 111 % for moisture content, respectively. There were significant differences among 105 families for all traits except moisture content. The high heritability estimate was found for height (0.4-0.69) and basic density (0.27-0.59). Applying 80% selection intensity on diameter and leaving 84 best families in each block will produce a high total genetic gain. Pilodyn penetration had negative correlation with diameter, wood density, and specific gravity.